Characterisation of void and fiber distribution in 3D printed carbon-fiber/PEEK using X-ray computed tomography. (October 2021) - Sommacal, S.; Matschinski, A.; Drechsler, K.; Compston, P.
Graphical abstract: Highlights: State-of-the-art micro-CT to acquire high resolution images of CF/PEEK material. Microstructure characterisation of feedstock filament and five 3D printed samples. Voids and fibers mapped and visualised in 3D, individual total amounts quantified. Effect of key 3D printing parameters on void content assessed. Effect of printing depositional process on internal geometry shown. Abstract: A detailed analysis of the microstructure of five 3D printed CF/PEEK samples and the commercial feedstock material used to produce them has been conducted by the means of state-of-the-art micro-CT imaging. The images unequivocally show that both feedstock filament and printed samples contain a large quantity of voids heterogeneously distributed. Voids are randomly distributed within the feedstock, while they are aligned in rows parallel to the mould plate within the printed samples. Short fibers are heterogeneously distributed and display a preferential alignment in all specimens. Overall, the results showed that the 3D printing process did not remove the voids originally present in the feedstock filament and varying key printing parameters had only a minor effect on the printed samples' void content, while the depositional nature of the printing process strongly affected the samples' internal geometry.